Dynamic Properties Influence the Perception of Facial Expressions. (November 2013) - Kamachi, Miyuki; Bruce, Vicki; Mukaida, Shigeru; Gyoba, Jiro; Yoshikawa, Sakiko; Akamatsu, Shigeru
Two experiments were conducted to investigate the role played by dynamic information in identifying facial expressions of emotion. Dynamic expression sequences were created by generating and displaying morph sequences which changed the face from neutral to a peak expression in different numbers of intervening intermediate stages, to create fast (6 frames), medium (26 frames), and slow (101 frames) sequences. In experiment 1, participants were asked to describe what the person shown in each sequence was feeling. Sadness was more accurately identified when slow sequences were shown. Happiness, and to some extent surprise, was better from faster sequences, while anger was most accurately detected from the sequences of medium pace. In experiment 2 we used an intensity-rating task and static images as well as dynamic ones to examine whether effects were due to total time of the displays or to the speed of sequence. Accuracies of expression judgments were derived from the rated intensities and the results were similar to those of experiment 1 for angry and sad expressions (surprised and happy were close to ceiling). Moreover, the effect of display time was found only for dynamic expressions and not for static ones, suggesting that it was speed, not time, which was responsible for these effects. These results suggest that representations of basic expressions of emotion encode information about dynamic as well as static properties.